The Influence of Marketing Mix Strategy on Supermarket Customer Satisfaction in Banyuwangi - Rizki Amelia, Rodhiah; Maimunah, Maimunah; Raditya Akbar, Nanda; Qomariah, Nurul; Thamrin, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The purpose of this research is to determine the Marketix Mic strategy for customer satisfaction at Akira Our Shop Banyuwangi. The independent variables in this research include product (X1), place (X2). promotion (X3) price (X4), and while the dependent variable is customer satisfaction (Y). The population in this study were all customers at Akira Our Shop Banyuwangi. The number of samples was determined as 30 respondents. The measurement scale in this study uses five levels in scores from 1-5. Descriptive analysis was carried out to explain respondents and research variables. Analysis of validity tests and reliability tests was carried out to test research measuring instruments. Based on the results of the analysis regarding the influence of the marketing mix which includes product (X1), place (X2). promotion (X3) price (X4), on customer satisfaction at Akira Our Shop Banyuwangi, the results are that product (X1), place (X2) and price (X4) have a significant effect on the level of customer satisfaction. Meanwhile promotion (X3) does not provide customer satisfaction.